SKRINING AMILASE, LIPASE DAN PROTEASE DARI BAKTERI ENDOFIT DAUN CIPLUKAN (Physalis angulata L.) - Nursanti, Oktavia Widya; Astuti, Winni; Ruga, Ritbey (Jurusan Kimia FMIPA UNMUL, 2022)
Endophytic bacteria is one of the source of extracellular enzymes producer. Enzymes that produced by endophytic bacteria are more beneficial because they can be cultured in small spaces with big quantities, relatively fast time and cheaper production costs compared to the sources of enzyme from plants and animals. This study was conducted to obtain amylase, lipase and protease from endophytic bacteria of ciplukan leaves (Physalis angulata L.). The research method used is experimental, by isolating endophytic bacteria from ciplukan leaves (Physalis angulata L.) in Nutrient Agar (NA) media and screening tests of extracellular enzyme activity from endophytic bacteria isolates. The isolation results was obtained 24 endophytic bacteria isolates that 4 bacteria isolates produce amylase, 3 bacteria isolates produce lipase and 2 bacteria produce protease.